2020
DOI: 10.26565/2410-7360-2020-53-16
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of the tourism development in terms of water crisis (case study of Iran)

Abstract: The objectives of this paper are to clarify how valuable natural resources associated with tourism industry are; to assess efficiency of the relation between water resources and sustainable development of tourism industry; to promote ecofriendly skills of visitors in order to have an interactive relationship with tourism assets; to maximize economic, social and environmental benefits for both local communities and tourists; to find out the value of Iran’s experience with tourism development with conservation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
2
0
1
Order By: Relevance
“…However, studies have not investigated reported changes in preferences during travel, and how they relate to cognitive, affective, and neuropsychological personality factors. In our previous papers we have considered an integral assessment of ethnic tourism in Ukraine [ 57 ], the current state of child and youth tourism development in Ukraine [ 58 ], perspectives of tourism development in terms of the water crisis in Iran [ 59 ], features of pilgrimage [ 60 ], and rural tourism in Ukraine [ 61 ]. Adding an investigation of both external and internal factors that affect tourism under crises such as the COVID-19 pandemic will add significantly to our previous efforts.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have not investigated reported changes in preferences during travel, and how they relate to cognitive, affective, and neuropsychological personality factors. In our previous papers we have considered an integral assessment of ethnic tourism in Ukraine [ 57 ], the current state of child and youth tourism development in Ukraine [ 58 ], perspectives of tourism development in terms of the water crisis in Iran [ 59 ], features of pilgrimage [ 60 ], and rural tourism in Ukraine [ 61 ]. Adding an investigation of both external and internal factors that affect tourism under crises such as the COVID-19 pandemic will add significantly to our previous efforts.…”
Section: Introductionmentioning
confidence: 99%
“…Джемалі Сарі 1 д. геогр. н., професор кафедри географії, 1 Університет Акденіз, Анталія, Туреччина, Катерина Сегіда 2 д. геогр. н., професор, кафедра соціально-економічної географії і регіонознавства імені Костянтина Нємця, 2 Харківський національний університет імені В. Н. Каразіна, Харків, Україна, Гамзе Чакір 1 магістр географії, асистент кафедри географії, Євгенія Телебєнєва 2 к. геогр.…”
Section: особливості залучення місцевої громади у розвиток соціальног...unclassified
“…In this context, it is crucial to prioritize social tourism to realize sustainable and accessible tourism activities. Therefore, when the relevant literature is scanned, it is seen that there are many studies on tourism on a national and international scale [1,10,17], but research on social tourism is limited. Social tourism is defined as a phenomenon or relationship that emerges when disadvantaged groups or economically weak segments within society participate in tourism activities [39].…”
mentioning
confidence: 99%